Conceptual Framework of Environmental, Social, and Governance (ESG) Research: Trends, Themes, and Emerging Perspectives - Ali Basah, Mohamad Yazis; Marzuki, Ainulashikin; Ramli, Nur Ainna; Mat Nor, Fauzias; Ab. Aziz, Muhammad Ridhwan; Shahwan, Syahidawati; Sabri, Hisham (The Journal of Muamalat and Islamic Finance Research, 2024)
This paper aims to assessing the growth and publication patterns in environmental, social and governance (ESG) research, identifying the main issues discussed among influential publications and authors that have shaped the discourse, and exploring the intersection of ESG with other emerging fields or trends. Data from the SCOPUS database were used in this study. The ‘biblioshiny’ R package, also known as ‘bibliometrix 3.0’, was employed to conduct bibliometric analysis, utilising mapping and clustering techniques on 1736 articles, in order to distil the comprehensive knowledge and identify emerging trends in ESG topics. The thematic Map classifies the ESG themes into niche themes (e.g., ESG investing, socially responsible investment, and ESG rating); emerging/declining themes (e.g., Sustainable development, corporate sustainability, and responsible investment); and basic/transversal themes (e.g., ESG, sustainability and CSR). Environmental, social, and governance imply a position between niche themes and motor themes, while the corporate social responsibility, corporate governance, and ESG performance implies a position between motor themes and basic themes. This study sheds light on the nature and patterns of ESG research. Citation rates are estimated by analysis, and journal impact factors are quantifiable and objective measures directly related to published research.